2016
DOI: 10.1186/s12872-016-0316-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved hyponatremia after pericardial drainage in patients suffering from cardiac tamponade

Abstract: BackgroundSome case reports showed unexplained hyponatremia in patients with cardiac tamponade. Reversible hyponatremia was observed in these patients who received pericardial drainage. The occurrence rate of hyponatremia in patients of cardiac tamponade is not clearly known. The objective of this study was to identify the relationship between hyponatremia, cardiac tamponade and their underlying diseases.MethodsWe reviewed the clinical data of patients with cardiac tamponade and receiving pericardial drainage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…All cases had mild to moderate hyponatraemia (>120 mmol/L) 77. However, in non-malignant cases they did not find any significant improvement in serum sodium levels postpericardiocentesis 7.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…All cases had mild to moderate hyponatraemia (>120 mmol/L) 77. However, in non-malignant cases they did not find any significant improvement in serum sodium levels postpericardiocentesis 7.…”
Section: Discussionmentioning
confidence: 87%
“…Among these, 35% cases were of malignant pericardial effusion and were strongly associated with hyponatraemia and showed significant improvement following pericardiocentesis 7. However, in non-malignant cases they did not find any significant improvement in serum sodium levels postpericardiocentesis 7. In contrast, Chang et al showed significant improvement in hyponatraemia in both malignant and benign cases of cardiac tamponade.…”
Section: Discussionmentioning
confidence: 97%
“…Pericardial effusion-associated hyponatremia has been described in previous case reports [ 2 6 ] and retrospective studies [ 7 , 8 ]. In most patients, hyponatremia resolves following medical management or pericardiocentesis.…”
Section: Discussionmentioning
confidence: 91%
“…Pericardial effusion represents a rare cause of reversible hyponatremia; this has been described in several case reports [ 2 6 , 9 ] and two retrospective reviews [ 7 , 8 ]. Our patient presented with progressively worsening hyponatremia in the setting of pericardial effusion with early tamponade and experienced rapid and complete normalization of serum sodium concentration following pericardiocentesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation